PENGARUH MEDIA PEMBELAJARAN BAHAN ALAM DAN TEMAN SEBAYA TERHADAP HASIL BELAJAR IPAS SISWA DIKELAS V SEKOLAH DASAR - Indri Yantidesi; Jamaris Jamna; Sandra Sukmaning Adji (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to prove the influence of learning media based on natural materials and peers on the learning outcomes of Natural and Social Sciences (IPAS) students in grade V elementary schools. This type of quasi-experimental research with a Purpose Sampling design. The research sample consisted of two classes, namely the experimental class which implemented learning using natural materials and peers as media, and the control class which did not use learning based on natural materials and peers. The instruments used include pretest and posttest to determine learning outcomes to measure cognitive aspects and then a questionnaire to see the influence of peers in learning. Data analysis was carried out using the t-test on the variable Natural Media Utilization with a calculated t-value of 2.869 and a sig value of 0.024. From these results it can be seen that t-count > t-table or 2,869 > 1,765, meaning that Ha is accepted and H0 is rejected, so the hypothesis in this research is that there is an influence of the use of learning media based on natural materials and peers on learning outcomes in Natural Sciences subjects and Social Sciences (IPAS) for fifth grade elementary school students. The research results show that learning media based on natural materials and peers can significantly improve learning outcomes. This research concludes that learning media based on natural materials, combined with a peer approach, is effective in improving science learning outcomes.